354 ASAS-EAAP Talk: The subclinical non-aureus staphylococcal mastitis in dairy cows: a lipidomics approach. (30th November 2020) - Ceciliani, Fabrizio; Audano, Matteo; Addis, Filippa; Mitro, Nico; Caruso, Donatella; Lecchi, Cristina; Ghaffari, Morteza Hosseini; Albertini, Mariangela; Tangorra, Francesco; Bronzo, Valerio
Abstract: This study aims to determine the untargeted lipidome of cow milk during non-staphylococcal sub-clinical mastitis. Dairy cow mastitis severely impacts the dairy industry by reducing milk yield and quality and increasing culling rate. Among the pathogens that cause bovine sub-clinical mastitis, non-aureus staphylococci (NAS) have become the most frequently isolated bacteria from milk samples. The molecular mechanisms regulating the mammary gland inflammatory responses to NAS are unclear. Although the application of system biology approaches to mastitis has provided pivotal information by investigating the transcriptome, proteome, and metabolome, the milk lipidome remains undisclosed. We determined the lipidome of 17 dairy cows with NAS sub-clinical mastitis (SM) and we compared the results with the lipidome of the milk of 13 healthy cows. The study was carried out following a liquid chromatography–quadrupole time-of-flight mass spectrometry (LC-QTOF-MS) approach. Sixteen subclasses of lipids were identified in both groups of animals. From 2, 506 measured lipids, 631 were significantly changed more than 10 folds (FDR < 0.01 in milk from cows with mastitis as compared to healthy cows. Our results point out the significant influence of NAS on the milk lipidome, contribute to the understanding of inflammatory processes in the bovine udder, and highlight potential novel biomarkers for improving mastitis diagnosis. Part of this work was carried out in "OMICs", an advanced mass spectrometry platform established by the Università degli Studi di Milano.